The Majelis Taklim Strategy in Developing Non-Formal Islamic Education in Sorong Raya, Southwest Papua, Indonesia - Rafiul Amri; Suparto Iribaram; Bambang Sunatar; Hasbullah Hasbullah; Abd. Rahman (Yayasan Haiah Nusratul Islam, 2026)
This study employed the strategies of Majelis Taklim in developing non-formal Islamic education in Sorong Raya, Eastern Indonesia. Using a qualitative approach, data were collected through observation, documentation, and semi-structured interviews with 12 participants from five Islamic organizations: Koordinator Pengajian Wanita Islam (KPWI) Kota Sorong, Badan Kontak Majelis Taklim (BKMT) Kabupaten Sorong, Majelis Taklim Marstussolihah Malawele, Majelis Taklim Muslimat Sorong, and Majelis Taklim Fatayat Sorong. The data were analysed using an interactive model of qualitative data analysis through simplifying reduction, organizing similar codes categorization, interpretation, and verification. The findings show that Majelis Taklim serves not only as a religious learning forum but also as an agent of social transformation by strengthening Islamic literacy, women’s empowerment, community solidarity, and religious moderation within a multicultural Muslim-minority context. This study contributes to non-formal Islamic education scholarship by highlighting contextual strategies for sustaining Islamic educational values in plural societies and offers practical implications for enhancing religious awareness, social cohesion, and community-based Islamic education.